МАКЕДОНСКИЕ ИСТОЧНИКИ СЛОВАРЕЙ Ф. МИКЛОШИЧА (Филолошке студије, 2019)
This paper deals with the Macedonian sources present in the dictionaries by Franc Mikloshich (1813–1891). The material from the Lexicon palaeoslovenicograeco-latinum emendatum auctum, published in Vienna 1862–1865 (further referred as Lexicon) and from Etymologisches Wörterbuch der Slavichen Sprachen, published in Vienna in 1886 (further referred as Etymological Dictionary) is analyzed in this work. The Old-Slavonic Dictionary, i.e. Lexicon has been the sole dictionary until now that uses sources from the Old-Slavonic Canon period and from all the redaction of the Church-Slavonic language for excerpting material, which means that this dictionary covers manuscripts written during a period of eight centuries (from 11th to 18th century). Considering the period when dictionaries were written it is clear that under the caption Bulg. – i.e. Bulgarisch, not only the Bulgarian but the Macedonian sources are hidden as well. In the review of sources given on the front pages of the Lexicon, one can recognize the renowned representative works of the Macedonian redaction of the Church-Slavonic language such as The Apostle of Ohrid (APOST.–OCHR.), The Psalter of Bologna (BON.), The Gospel of Radomir (EV.–MIH.), 13th century and the Apostle of Strumica (STRUM.) from 13th century. In addition to these, the records in the margins in some of the manuscripts can be treated as Macedonian sources. In the Etymological Dictionary of Slavonic languages, the following Macedonian sources were used: Miladinovci, Bxlgarski народни песни (mil.b.); Verković, Narodne pesme makedonskih Bugara (verk.b.) and Wörter aus dem apokryphen «veda» (vc.b.). It is clear that these all are well-known collections of Macedonian folk songs, the first one compiled by Miladinovci, the second one by Verković, and the latter source is the well-known Veda Slovena, a mystification written in South-eastern Macedonian dialect. In this paper some comparisons with the latest findings of the Macedonian historical lexicography are drawn.